Scale inhibitor and dispersant, preparation method and application thereof

By using a combination of mesoporous silica composite, citric acid, sodium tanninate and polyepoxysuccinic acid, the problems of low solubility and single scale inhibition mechanism in high-temperature water environments are solved, and the problem of low solubility of existing scale inhibitors in high-temperature water environments is achieved. Efficient and stable scale inhibition effect at high temperatures.

CN119191582BActive Publication Date: 2025-02-07CHENGDU NAHAICHUAN ENVIRONMENTAL ENG CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411747133.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-02
Publication Date
2025-02-07
Estimated Expiration
2044-12-02

AI Technical Summary

Technical Problem

The existing environmentally friendly scale inhibitors have low solubility in high-temperature water environments, a single scale inhibition mechanism and are not effective enough. Especially when multiple scale-forming ions and pollutants coexist, their stability and scale inhibition effects are insufficient.

Method used

Using mesoporous silica composite as the main component, combining citric acid, sodium tanninate and polyepoxysuccinic acid, carbon quantum dots are embedded in mesoporous silica and coated with chitosan-polyethylene glycol. Graft copolymers form a scale inhibitor dispersant that is more resistant to high temperatures, stable and has better scale inhibition effect at a smaller amount.

Benefits of technology

A high scale resistance is achieved in a high temperature water environment above 100°C, ensuring sufficient scale resistance effect with a small amount, and the scale resistance dispersant is stable and environmentally friendly at high temperatures.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention provides a scale inhibitor and dispersant, a preparation method and application thereof, and belongs to the technical field of water treatment. The prepared mesoporous silica composite material takes mesoporous silica as the main framework, carbon quantum dots are embedded in the mesopores, and the surface is coated with a chitosan-polyethylene glycol graft copolymer. The coated chitosan-polyethylene glycol graft copolymer is used to block external liquid, so that the carbon quantum dots in the mesopores can remain stable at high temperatures. The chitosan-polyethylene glycol graft copolymer is easy to expand or change conformation at high temperatures, and can be combined with sodium tannate and the like to achieve uniform slow release of the carbon quantum dots at high temperatures and maintain sufficient dispersibility, thereby ensuring good scale inhibition performance at high temperatures, thereby meeting the needs of high-temperature and high-pressure industrial water environments such as steam boilers.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of water treatment, and in particular relates to a scale inhibitor and dispersant, a preparation method and application thereof. Background Art

[0002] Industrial recycling water refers to a water use method that reduces fresh water consumption and wastewater discharge by reusing and recycling water resources during industrial production. This water use model helps save water resources, reduce water treatment costs, reduce environmental pollution, and improve the efficiency and sustainability of industrial production.

[0003] In the process of industrial circulating water, scale is a problem that cannot be ignored. The formation of scale will not only reduce the heat exchange efficiency and increase energy consumption, but also may cause equipment damage, production interruption and increased maintenance costs. At present, the use of scale inhibitors is an economical and effective technical means to control chemical scaling in the process of industrial circulating water. There are three main types of commonly used chemical scale inhibitors: phosphorus-containing scale inhibitors, copolymer scale inhibitors and environmentally friendly scale inhibitors. Among them, phosphorus-containing scale inhibitors include inorganic phosphorus and organic phosphine-based scale inhibitors, which have been widely used due to their excellent scale inhibition performance. In recent years, the use of such scale inhibitors is gradually being restricted because they are rich in phosphorus and easily cause eutrophication of water bodies and aggravate microbial corrosion of pipe networks. Copolymer scale inhibitors such as polycarboxylic acids, phosphinocarboxylic acid polymers and polymers containing sulfonic acid groups have good scale inhibition performance and biodegradability, but long-term accumulation can easily lead to water pollution and pose a threat to human health. Environmentally friendly scale inhibitors, such as polyepoxysuccinic acid (PESA) and polyaspartic acid (PASP) and their derivatives, plant extracts and their derivatives, and carbon nanoparticle scale inhibitors, have become a research hotspot because of their biodegradable, non-toxic, and almost no pollution to the environment. These new environmentally friendly scale inhibitors can not only effectively control the formation of scale, but also reduce the impact on the environment, representing the green development direction of scale inhibition technology in the field of water treatment.

[0004] Nevertheless, the current environmentally friendly scale inhibitors still face certain challenges when used, mainly manifested in: polyaspartic acid (PASP) and polyepoxysuccinic acid (PESA) will encounter solubility problems in water environments with high alkalinity and hardness, affecting their scale inhibition performance, and their scale inhibition mechanism is relatively simple, which is not effective enough when facing complex water chemical environments, especially when multiple scale-forming ions and pollutants coexist; plant extracts and their derivatives have poor stability in high-temperature and high-pressure industrial environments, and there is a problem of high extraction and purification process costs; carbon nanoparticles such as carbon quantum dot scale inhibitors have unique scale inhibition properties, but in order to achieve a better scale inhibition effect under high temperature conditions, the dosage will be relatively large, and with the increase of temperature, the agglomeration of carbon quantum dots will increase significantly, resulting in a decrease in scale inhibition effect. This may be because high temperature will intensify the thermal motion of nanoparticles, thereby increasing the chances of contact and aggregation between them.

[0005] In view of the above problems, the use of environmentally friendly scale inhibitors in industrial circulating water is limited. For example, taking steam boilers as an example, the temperature of its supply water and return water is generally between 100-150℃. Under such high temperature conditions, traditional environmentally friendly scale inhibitors may not provide sufficient scale inhibition effect. Therefore, it is necessary to develop more high temperature resistant, more stable, better scale inhibition effect and environmentally friendly scale inhibitors that are used in less amount to meet the needs of high temperature and high pressure industrial water environments such as steam boilers. Summary of the invention

[0006] In order to solve the problems existing in the prior art, the present invention provides a scale inhibitor and dispersant, a preparation method and application thereof, to solve one of the above problems.

[0007] In order to achieve the above technical objectives, the present invention adopts the following technical solutions:

[0008] A scale inhibitor dispersant comprises at least the following raw material components by weight: 15-20 parts of a mesoporous silica composite material, 5-8 parts of citric acid, 0.2-0.5 parts of sodium tannate, 8-12 parts of polyepoxysuccinic acid and 70-80 parts of deionized water, wherein the mesoporous silica composite material comprises mesoporous silica and a chitosan-polyethylene glycol graft copolymer at least partially coated on the surface of the mesoporous silica, the chitosan-polyethylene glycol graft copolymer accounts for 5%-10% of the total weight of the mesoporous silica composite material, and carbon quantum dots are embedded in the mesopores of the mesoporous silica.

[0009] Wherein, the mesoporous silica composite material is prepared by the following method:

[0010] Preparation of mesoporous silica with a mesoporous structure;

[0011] A pure carbon quantum dot solution is obtained;

[0012] Adding the prepared mesoporous silica to the pure carbon quantum dot solution to embed the carbon quantum dots into the pores of the mesoporous silica;

[0013] A chitosan-polyethylene glycol graft copolymer is prepared and coated on the surface of mesoporous silica embedded with carbon quantum dots, thereby obtaining the mesoporous silica composite material.

[0014] Compared with the prior art, the present invention has at least the following beneficial effects:

[0015] The present invention achieves a high scale inhibition rate at high temperature by preparing a mesoporous silica composite material and using citric acid, sodium tannate and polyepoxysuccinic acid, so that the formula of the present invention can be applied to a high-temperature water environment above 100°C and can have a sufficient scale inhibition effect with a small amount of use; the prepared mesoporous silica composite material uses mesoporous silica as the main framework, is not easy to decompose and destroy at high temperature, carbon quantum dots are embedded in the mesopores of the mesoporous silica, and the surface of the mesoporous silica is coated with chitosan-polyethylene glycol graft copolymer. In this way, carbon quantum dots can be stored in the mesopores of mesoporous silica, and the external liquid can be blocked by the coated chitosan-polyethylene glycol graft copolymer, so that the carbon quantum dots in the mesopores can remain stable at high temperatures. In addition, since the molecular segments of the chitosan-polyethylene glycol graft copolymer will stretch and expand at high temperatures, this helps to release the carbon quantum dots uniformly at high temperatures. The slowly released carbon quantum dots have sufficient dispersibility under the action of sodium tannate and the like, and therefore have sufficient scale inhibition effect. In general, through the ratio of each component and the synergistic effect between the components, the present invention proposes a scale inhibitor dispersant that is more resistant to high temperatures, more stable, has better scale inhibition effect at a lower usage amount, and is environmentally friendly. DETAILED DESCRIPTION

[0016] In view of the defects of the prior art, the inventor of this case has proposed the technical solution of the present invention after long-term research and extensive practice. The technical solution of the present invention will be described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0017] Specifically, the present invention provides a scale inhibitor dispersant, which comprises at least the following raw material components in parts by weight: 15 to 20 parts of a mesoporous silica composite material, 5 to 8 parts of citric acid, 0.2 to 0.5 parts of sodium tannate, 8 to 12 parts of polyepoxysuccinic acid (PESA) and 70 to 80 parts of deionized water, wherein the mesoporous silica composite material comprises mesoporous silica and a chitosan-polyethylene glycol graft copolymer at least partially coated on the surface of the mesoporous silica, the chitosan-polyethylene glycol graft copolymer accounts for 5% to 10% of the total weight of the mesoporous silica composite material, and carbon quantum dots are embedded in the mesopores of the mesoporous silica.

[0018] The scale inhibitor dispersant is prepared by the following method:

[0019] S1. Preparation of mesoporous silica composite materials

[0020] S11. Solution preparation

[0021] Use a container to measure an appropriate amount of deionized water, add hexadecyltrimethylammonium bromide (CTAB), stir to completely dissolve it, and prepare a CTAB aqueous solution. The concentration of CTAB is controlled at 0.1~0.2mol / L;

[0022] In another container, concentrated ammonia water (mass fraction of about 25%-28%) is mixed with deionized water to prepare a dilute ammonia solution, the ammonia concentration of the dilute ammonia solution is about 1-2 mol / L;

[0023] S12. Preparation of mesoporous silica precursor

[0024] Under vigorous stirring (e.g., mechanical stirring speed of 1000-1200rpm), tetraethyl orthosilicate (TEOS) is slowly added dropwise to the CTAB aqueous solution, the molar ratio of TEOS to CTAB is about 1:0.1-0.12, and after the addition is completed, stirring is continued for 15-30 minutes to obtain a uniformly mixed solution; then, the prepared ammonia solution is added dropwise to the mixed solution, the reaction temperature is controlled at 30-35°C, and the reaction is continuously stirred for 2-3 hours. During this process, a white precipitate will gradually form in the mixed solution, which is the precursor of mesoporous silica;

[0025] S13, obtaining mesoporous silica

[0026] After the preparation of the precursor of mesoporous silica is completed, the reaction solution is filtered to collect the white precipitate; in this process, the precipitate is repeatedly washed with a large amount of deionized water until the pH value of the filtrate is close to neutral to remove residual impurities such as ammonia water and CTAB; then, the washed white precipitate is dried in an oven at 80-100° C. for 10-12 hours to remove residual moisture; then, the dried precipitate is calcined in a muffle furnace at 500-550° C. for 4-5 hours to remove the CTAB template and obtain mesoporous silica with a mesoporous structure;

[0027] S14. Synthesis of Carbon Quantum Dots

[0028] Anhydrous citric acid and L-lysine are placed in a polytetrafluoroethylene liner of a high-pressure reactor in a certain molar ratio (preferably, anhydrous citric acid: L-lysine = 10-15:1) and stirred evenly, and an appropriate amount of deionized water is added to make the concentration of citric acid about 0.5 mol / L, and the high-pressure reactor is sealed and reacted at 180°C for 8 hours (during this process, air can be introduced in an appropriate amount to promote the carbonization reaction). After the reaction is completed, it is naturally cooled to room temperature to obtain a primary carbon quantum dot solution; then, the primary carbon quantum dot solution is dialyzed to remove unreacted impurities and small molecules to obtain a pure carbon quantum dot solution; during dialysis, a dialysis bag with a molecular weight cutoff of 1000-2000Da is used, and the dialysis is performed in deionized water for 24-48 hours (this is conducive to the subsequent embedding and sustained release of carbon quantum dots);

[0029] S15. Embedding of carbon quantum dots

[0030] The mesoporous silica prepared in step S13 is added to the pure carbon quantum dot solution, the mass volume ratio of the mesoporous silica to the carbon quantum dot solution is controlled at 0.1 g / mL, and ultrasonic treatment is performed for 2-3 hours to allow the carbon quantum dots to fully enter the pores of the mesoporous silica; after the ultrasonic treatment, vacuum drying is performed at 60-70° C. for 8-10 hours to obtain mesoporous silica with carbon quantum dots embedded in the mesopores;

[0031] S16. Preparation of chitosan-polyethylene glycol graft copolymer

[0032] S161, weighing an appropriate amount of chitosan, dissolving it in a dilute acetic acid solution to prepare a chitosan solution with a mass fraction of 2% to 3% (during the dissolution process, it can be appropriately heated to, for example, 40 to 50° C. and stirred to promote the dissolution of chitosan); weighing a certain amount of polyethylene glycol (PEG, the molecular weight can be selected as required, such as 1000 to 2000), dissolving it in an appropriate amount of an organic solvent (such as dimethyl sulfoxide DMSO) to prepare a polyethylene glycol solution, the mass fraction of polyethylene glycol is about 5% to 10%;

[0033] S162, slowly dropwise adding the polyethylene glycol solution prepared in step S161 into the chitosan solution, the mass ratio of the polyethylene glycol solution to the chitosan solution being controlled at 0.4-0.5:1, and at the same time, adding an appropriate amount of catalyst (such as a carbodiimide catalyst), the amount of the catalyst being 0.1%-0.2% of the mass of the chitosan solution; stirring the reaction at room temperature for 6-8 hours under nitrogen protection (during the reaction, the degree of the reaction can be monitored by detecting the viscosity of the solution, infrared spectroscopy, etc.); after the reaction is completed, pouring the reaction solution into a large amount of acetone to precipitate the graft copolymer; filtering and collecting the precipitate and washing it with acetone for multiple times to remove impurities such as unreacted polyethylene glycol and catalyst, and then vacuum drying at 50-60° C. for 6-8 hours to obtain a chitosan-polyethylene glycol graft copolymer;

[0034] S17, coated mesoporous silica

[0035] S171, dissolving the prepared chitosan-polyethylene glycol graft copolymer in deionized water to prepare a copolymer solution with a mass fraction of 5% to 8%; preferably, during the dissolution process, the copolymer solution is heated to 40° C. and ultrasonically treated for 10 to 15 minutes to promote rapid dissolution;

[0036] S172, adding the mesoporous silica having carbon quantum dots embedded in the mesopores to the copolymer solution at room temperature, and stirring at a stirring speed of 200-300 rpm for 2-4 hours, so that the surface of the mesoporous silica is evenly coated with the graft copolymer (within this stirring speed range, the carbon quantum dots will not escape due to stirring); during the stirring process, taking a small amount of sample every 1 hour, and observing the coating condition of the surface of the mesoporous silica under a microscope to ensure uniform coating;

[0037] S173. Collect the coated mesoporous silica composite material by centrifugation (speed 3000-5000 rpm, time 10-15 minutes), and wash it with deionized water 3-5 times to remove the uncoated graft copolymer, the amount of deionized water used each time is about 2-3 times the volume of the coated mesoporous silica composite material; then dry it at 50-60°C for 4-6 hours to obtain the mesoporous silica composite material; it should be noted that after obtaining the mesoporous silica composite material, it is also necessary to use thermogravimetric analysis (TGA) or other analytical techniques to Quality inspection to verify the actual mass proportion of chitosan-polyethylene glycol graft copolymer in the mesoporous silica composite material, such as 5%, 6%, 8%, 10%, etc. If the actual mass proportion of chitosan-polyethylene glycol graft copolymer in the mesoporous silica composite material does not meet the predetermined requirements, it is necessary to readjust the mass fraction of chitosan-polyethylene glycol graft copolymer in the copolymer solution, as well as the stirring speed and stirring time during coating, and perform a new coating operation until the mass proportion of chitosan-polyethylene glycol graft copolymer in the mesoporous silica composite material meets the requirements;

[0038] S2. Mixed preparation of scale inhibitor and dispersant

[0039] According to the ratio of the raw material components of the scale inhibitor dispersant, citric acid, sodium tannate, polyepoxysuccinic acid and deionized water are mixed, and a mechanical stirrer is used to stir at a speed of 400-500rpm for 10-15 minutes to uniformly disperse the citric acid, sodium tannate and polyepoxysuccinic acid in the deionized water; then, the mesoporous silica composite material prepared in step S1 is added, and stirred for another 10-15 minutes to fully mix the components to obtain the scale inhibitor dispersant. The polyepoxysuccinic acid selected in the present invention is purchased from JXL-108 polyepoxysuccinic acid of Xinxiang Juxinglong Water Treatment Co., Ltd. In this step, the use of deionized water is mainly to ensure that the components are mixed evenly, and no dissolution is required in subsequent use, and it can be quickly dispersed into the circulating water system. Deionized water itself does not play a role in scale inhibition and dispersibility.

[0040] Embodiment 1

[0041] A scale inhibitor dispersant, which comprises at least the following raw material components by weight: 15 parts of a mesoporous silica composite material, 5 parts of citric acid, 0.2 parts of sodium tannate, 8 parts of polyepoxysuccinic acid and 70 parts of deionized water, wherein the mesoporous silica composite material comprises mesoporous silica and a chitosan-polyethylene glycol graft copolymer at least partially coated on the surface of the mesoporous silica, the chitosan-polyethylene glycol graft copolymer accounts for 8% of the total weight of the mesoporous silica composite material, and carbon quantum dots are embedded in the mesopores of the mesoporous silica. In the first embodiment, the scale inhibitor dispersant is prepared according to the aforementioned scale inhibitor dispersant preparation method, and in the carbon quantum dot synthesis step, the molar ratio of anhydrous citric acid to L-lysine is 12:1.

[0042] Embodiment 2

[0043] A scale inhibitor dispersant, which comprises at least the following raw material components by weight: 18 parts of a mesoporous silica composite material, 5 parts of citric acid, 0.2 parts of sodium tannate, 8 parts of polyepoxysuccinic acid and 70 parts of deionized water, wherein the mesoporous silica composite material comprises mesoporous silica and a chitosan-polyethylene glycol graft copolymer at least partially coated on the surface of the mesoporous silica, the chitosan-polyethylene glycol graft copolymer accounts for 8% of the total weight of the mesoporous silica composite material, and carbon quantum dots are embedded in the mesopores of the mesoporous silica. In the second embodiment, the scale inhibitor dispersant is prepared according to the aforementioned scale inhibitor dispersant preparation method, and in the carbon quantum dot synthesis step, the molar ratio of anhydrous citric acid to L-lysine is 12:1.

[0044] Embodiment 3

[0045] A scale inhibitor dispersant, which comprises at least the following raw material components by weight: 20 parts of a mesoporous silica composite material, 5 parts of citric acid, 0.2 parts of sodium tannate, 8 parts of polyepoxysuccinic acid and 70 parts of deionized water, wherein the mesoporous silica composite material comprises mesoporous silica and a chitosan-polyethylene glycol graft copolymer at least partially coated on the surface of the mesoporous silica, the chitosan-polyethylene glycol graft copolymer accounts for 8% of the total weight of the mesoporous silica composite material, and carbon quantum dots are embedded in the mesopores of the mesoporous silica. In this embodiment three, the scale inhibitor dispersant is prepared according to the aforementioned scale inhibitor dispersant preparation method, and in the carbon quantum dot synthesis step, the molar ratio of anhydrous citric acid to L-lysine is 12:1.

[0046] Embodiment 4

[0047] A scale inhibitor dispersant, which comprises at least the following raw material components by weight: 18 parts of a mesoporous silica composite material, 5 parts of citric acid, 0.3 parts of sodium tannate, 8 parts of polyepoxysuccinic acid and 70 parts of deionized water, wherein the mesoporous silica composite material comprises mesoporous silica and a chitosan-polyethylene glycol graft copolymer at least partially coated on the surface of the mesoporous silica, the chitosan-polyethylene glycol graft copolymer accounts for 8% of the total weight of the mesoporous silica composite material, and carbon quantum dots are embedded in the mesopores of the mesoporous silica. In this fourth embodiment, the scale inhibitor dispersant is prepared according to the aforementioned scale inhibitor dispersant preparation method, and in the carbon quantum dot synthesis step, the molar ratio of anhydrous citric acid to L-lysine is 12:1.

[0048] Embodiment 5

[0049] A scale inhibitor dispersant, which comprises at least the following raw material components by weight: 18 parts of a mesoporous silica composite material, 5 parts of citric acid, 0.5 parts of sodium tannate, 8 parts of polyepoxysuccinic acid and 70 parts of deionized water, wherein the mesoporous silica composite material comprises mesoporous silica and a chitosan-polyethylene glycol graft copolymer at least partially coated on the surface of the mesoporous silica, the chitosan-polyethylene glycol graft copolymer accounts for 8% of the total weight of the mesoporous silica composite material, and carbon quantum dots are embedded in the mesopores of the mesoporous silica. In this embodiment 5, the scale inhibitor dispersant is prepared according to the aforementioned scale inhibitor dispersant preparation method, and in the carbon quantum dot synthesis step, the molar ratio of anhydrous citric acid to L-lysine is 12:1.

[0050] Embodiment 6

[0051] A scale inhibitor dispersant, which comprises at least the following raw material components by weight: 18 parts of a mesoporous silica composite material, 8 parts of citric acid, 0.5 parts of sodium tannate, 12 parts of polyepoxysuccinic acid and 80 parts of deionized water, wherein the mesoporous silica composite material comprises mesoporous silica and a chitosan-polyethylene glycol graft copolymer at least partially coated on the surface of the mesoporous silica, the chitosan-polyethylene glycol graft copolymer accounts for 8% of the total weight of the mesoporous silica composite material, and carbon quantum dots are embedded in the mesopores of the mesoporous silica. In this embodiment six, the scale inhibitor dispersant is prepared according to the aforementioned scale inhibitor dispersant preparation method, and in the carbon quantum dot synthesis step, the molar ratio of anhydrous citric acid to L-lysine is 12:1.

[0052] Embodiment 7

[0053] A scale inhibitor dispersant, which comprises at least the following raw material components by weight: 18 parts of a mesoporous silica composite material, 8 parts of citric acid, 0.5 parts of sodium tannate, 12 parts of polyepoxysuccinic acid and 80 parts of deionized water, wherein the mesoporous silica composite material comprises mesoporous silica and a chitosan-polyethylene glycol graft copolymer at least partially coated on the surface of the mesoporous silica, the chitosan-polyethylene glycol graft copolymer accounts for 8% of the total weight of the mesoporous silica composite material, and carbon quantum dots are embedded in the mesopores of the mesoporous silica. In this embodiment 7, the scale inhibitor dispersant is prepared according to the aforementioned scale inhibitor dispersant preparation method, and in the carbon quantum dot synthesis step, the molar ratio of anhydrous citric acid to L-lysine is 10:1.

[0054] Embodiment 8

[0055] A scale inhibitor dispersant, which comprises at least the following raw material components by weight: 18 parts of a mesoporous silica composite material, 8 parts of citric acid, 0.5 parts of sodium tannate, 12 parts of polyepoxysuccinic acid and 80 parts of deionized water, wherein the mesoporous silica composite material comprises mesoporous silica and a chitosan-polyethylene glycol graft copolymer at least partially coated on the surface of the mesoporous silica, the chitosan-polyethylene glycol graft copolymer accounts for 8% of the total weight of the mesoporous silica composite material, and carbon quantum dots are embedded in the mesopores of the mesoporous silica. In this embodiment eight, the scale inhibitor dispersant is prepared according to the aforementioned scale inhibitor dispersant preparation method, and in the carbon quantum dot synthesis step, the molar ratio of anhydrous citric acid to L-lysine is 15:1.

[0056] Embodiment 9

[0057] A scale inhibitor dispersant, which comprises at least the following raw material components by weight: 18 parts of a mesoporous silica composite material, 5 parts of citric acid, 0.2 parts of sodium tannate, 8 parts of polyepoxysuccinic acid and 70 parts of deionized water, wherein the mesoporous silica composite material comprises mesoporous silica and a chitosan-polyethylene glycol graft copolymer at least partially coated on the surface of the mesoporous silica, the chitosan-polyethylene glycol graft copolymer accounts for 5% of the total weight of the mesoporous silica composite material, and carbon quantum dots are embedded in the mesopores of the mesoporous silica. In this embodiment nine, the scale inhibitor dispersant is prepared according to the aforementioned scale inhibitor dispersant preparation method, and in the carbon quantum dot synthesis step, the molar ratio of anhydrous citric acid to L-lysine is 12:1.

[0058] Embodiment 10

[0059] A scale inhibitor dispersant, which comprises at least the following raw material components by weight: 18 parts of a mesoporous silica composite material, 5 parts of citric acid, 0.2 parts of sodium tannate, 8 parts of polyepoxysuccinic acid and 70 parts of deionized water, wherein the mesoporous silica composite material comprises mesoporous silica and a chitosan-polyethylene glycol graft copolymer at least partially coated on the surface of the mesoporous silica, the chitosan-polyethylene glycol graft copolymer accounts for 10% of the total weight of the mesoporous silica composite material, and carbon quantum dots are embedded in the mesopores of the mesoporous silica. In this embodiment 10, the scale inhibitor dispersant is prepared according to the aforementioned scale inhibitor dispersant preparation method, and in the carbon quantum dot synthesis step, the molar ratio of anhydrous citric acid to L-lysine is 12:1.

[0060] Comparative Example 1

[0061] Comparative Example 1 refers to Example 2, and the only difference is that in Comparative Example 1, the same weight of polyepoxysuccinic acid is used to replace the mesoporous silica composite material in Example 2; that is, its formula is: a scale inhibitor dispersant, which includes at least the following raw material components by weight: 5 parts of citric acid, 0.2 parts of sodium tannate, 26 parts of polyepoxysuccinic acid (18 parts + 8 parts) and 70 parts of deionized water. When preparing, citric acid, sodium tannate, polyepoxysuccinic acid and deionized water are directly mixed uniformly according to the proportion (refer to step S2).

[0062] Comparative Example 2

[0063] Comparative Example 2 refers to Example 2, and the only difference is that in Comparative Example 2, sodium tannate is not added, that is, its formula is: a scale inhibitor dispersant, which includes at least the following raw material components by weight: 18 parts of mesoporous silica composite material, 5 parts of citric acid, 8 parts of polyepoxysuccinic acid and 70 parts of deionized water, wherein the mesoporous silica composite material includes mesoporous silica and chitosan-polyethylene glycol graft copolymer at least partially coated on the surface of the mesoporous silica, the chitosan-polyethylene glycol graft copolymer accounts for 8% of the total weight of the mesoporous silica composite material, and carbon quantum dots are embedded in the mesopores of the mesoporous silica. The scale inhibitor dispersant is prepared according to the aforementioned scale inhibitor dispersant preparation method (sodium tannate is not added in the preparation method accordingly), and in the carbon quantum dot synthesis step, the molar ratio of anhydrous citric acid to L-lysine is 12:1.

[0064] Comparative Example 3

[0065] The formula of Comparative Example 3 refers to that of Example 2, with the only difference being that in the carbon quantum dot synthesis step of Comparative Example 3, the molar ratio of anhydrous citric acid to L-lysine is 5:1.

[0066] Comparative Example 4

[0067] The formula of Comparative Example 4 refers to that of Example 2, with the only difference being that in the carbon quantum dot synthesis step of Comparative Example 4, the molar ratio of anhydrous citric acid to L-lysine is 20:1.

[0068] Comparative Example 5

[0069] Comparative Example 5 refers to Example 2, but differs in that the same weight portions of polyepoxysuccinic acid are used to replace the mesoporous silica composite material, citric acid and sodium tannate in Example 2, that is, its formula is: a scale inhibitor dispersant, which comprises at least the following raw material components in parts by weight: 31.2 parts of polyepoxysuccinic acid (18+5+0.2+8) and 70 parts of deionized water. When preparing, the polyepoxysuccinic acid and deionized water are directly mixed evenly according to the proportion (refer to step S2).

[0070] Comparative Example 6

[0071] Comparative Example 6 refers to Example 2, the only difference being that the synthesis method of carbon quantum is different. In this Comparative Example 6, anhydrous citric acid and fumaric acid are prepared in a molar ratio of 12:1; other than this difference, the ratio of the raw material components and the preparation method are the same as those in Example 2.

[0072] Comparative Example 7

[0073] Comparative Example 7 refers to Example 2, the only difference being that the synthesis method of carbon quantum is different. In this Comparative Example 7, anhydrous citric acid and L-ascorbic acid are prepared in a molar ratio of 12:1; except for this difference, the ratio of the raw material components and the preparation method are the same as those in Example 2.

[0074] Comparative Example 8

[0075] Comparative Example 8 refers to Example 2, and the only difference is that polyepoxysuccinic acid is not added in this Comparative Example 8. Apart from this difference, the ratio of raw material components and the preparation method are the same as those of Example 2. That is, its formula is: a scale inhibitor dispersant, which includes at least the following raw material components by weight: 18 parts of mesoporous silica composite material, 5 parts of citric acid, 0.2 parts of sodium tannate and 70 parts of deionized water, wherein the mesoporous silica composite material includes mesoporous silica and chitosan-polyethylene glycol graft copolymer at least partially coated on the surface of the mesoporous silica, the chitosan-polyethylene glycol graft copolymer accounts for 8% of the total weight of the mesoporous silica composite material, and carbon quantum dots are embedded in the mesopores of the mesoporous silica. In this Comparative Example 8, the scale inhibitor dispersant is prepared according to the aforementioned scale inhibitor dispersant preparation method, and in the carbon quantum dot synthesis step, the molar ratio of anhydrous citric acid to L-lysine is 12:1.

[0076] Performance evaluation: The scale inhibition rate of calcium carbonate was tested here. The test referred to GB / T 16632-2019 "Determination of scale inhibition performance of water treatment agents - carbonate precipitation method". The static scale inhibition method was used to determine the effect of different scale inhibition dispersants on CaCO 3 The scale inhibition performance of the scale was tested and a blank test was performed, in which the Ca in the solution was controlled. 2+ and HCO 3 - The mass concentration of ions was 0.5 g / L, the pH was 10, and the water temperature was controlled at 80°C, 100°C, and 120°C for three groups of experiments. Each group of experiments was temperature controlled for 8 hours. During the experiment, distilled water at the same temperature was added to reduce the influence of water evaporation on the experimental results. Finally, the solution was cooled to room temperature, and the supernatant was taken to determine the Ca content in it by EDTA method. 2+ The calculation formula of concentration and scale inhibition rate is: Where, C 1 is the Ca measured after adding the scale inhibitor 2+ Ion concentration, mg / L; C 2 is the Ca in the initial solution 2+ Ion concentration, mg / L; C 0 is a blank sample without adding scale inhibitor, mg / L. When the scale inhibition rate of calcium carbonate is tested, the dosage of the scale inhibitor dispersant is tested when the mass concentration of the active ingredient after it is added to the test water is 20 mg / L (for example, taking Example 1 as an example, the total mass concentration of the mesoporous silica composite material, citric acid, sodium tannate and polyepoxysuccinic acid is 20 mg / L; taking Comparative Example 5 as an example, the mass concentration of the polyepoxysuccinic acid is 20 mg / L), and the following scale inhibition rate test results are obtained, as shown in Table 1:

[0077]

[0078] Table 1 - Calcium carbonate scale inhibition test results.

[0079] It can be seen from the above tests shown in Table 1 that the scale inhibition efficiency of the scale dispersants of Examples 1-10 on calcium carbonate scale at high temperatures is generally higher than that of Comparative Examples 1-8, especially at high temperatures of 100°C to 120°C. Among them, compared with Example 2, Comparative Example 1 uses the same weight of polyepoxysuccinic acid to replace the mesoporous silica composite material in Example 2, that is, the formula of Comparative Example 1 does not use a mesoporous silica composite material, and the main ingredients that play a scale inhibition role in its formula are citric acid and polyepoxysuccinic acid, and in an alkaline high temperature environment, the effect of citric acid on calcium carbonate scale inhibition is significantly lower than that of polyepoxysuccinic acid, which results in the scale inhibition rate of the formula of Comparative Example 1 under various temperature conditions (80°C~120°C) is lower than that of Example 2, and even lower than the scale inhibition rate of Comparative Example 5 (the effective scale inhibition ingredient in Comparative Example 5 is only polyepoxysuccinic acid). Further, referring to Comparative Example 2, its formula only does not add sodium tannate compared to Example 2. Through testing, it was found that in the absence of sodium tannate, even if mesoporous silica composite materials and polyepoxysuccinic acid were used, the scale inhibition rate of Comparative Example 2 was very low. This may be because sodium tannate promoted the sustained release of carbon quantum dots in the mesoporous silica composite materials, thereby enhancing the scale inhibition effect. At the same time, the dispersibility of sodium tannate helps to maintain the stability of the system. After the carbon quantum dots are released, sodium tannate can maintain the dispersion of the carbon quantum dots and avoid the occurrence of agglomeration, thereby further improving the scale inhibition effect. When sodium tannate is not added (Comparative Example 2), the carbon quantum dots in the mesoporous silica composite materials cannot be released (or very little is released), so the expected calcium carbonate scale inhibition effect cannot be achieved. In addition, in Comparative Example 2, by comparing the scale inhibition rates at 80°C, 100°C and 120°C, it can be found that with the increase of temperature, the scale inhibition rate increases instead. This may be because the high temperature causes a part of the carbon quantum dots in the mesoporous silica composite material to be released. Nevertheless, in the absence of sodium tannate, the release of such carbon quantum dots may be a small amount, or, although a large amount is released, the released carbon quantum dots agglomerate at high temperature, resulting in the formula of Comparative Example 2 having a relatively low scale inhibition rate at 100°C and 120°C (relative to Example 2). Furthermore, comparative examples 3 and 4 were tested for reference in preparing carbon quantum dots using anhydrous citric acid and L-lysine in different ratios. Compared with Example 2, it can be seen that the calcium carbonate scale inhibition effects of comparative examples 3 and 4 are reduced, indicating that the ratio of anhydrous citric acid and L-lysine also has a certain influence on the scale inhibition rate of the formula. In addition to the scale inhibition properties of the prepared carbon quantum dots themselves, this influence may also be affected by factors such as the release rate from the chitosan-polyethylene glycol graft copolymer and the synergistic effect with other components. Therefore, the test established that the optimal ratio of anhydrous citric acid and L-lysine under the formula of the present invention is a molar ratio of 10~15:1.Further, Comparative Examples 6 and 7 show the scheme of preparing carbon quantum dots by combining anhydrous citric acid with fumaric acid or L-ascorbic acid. By comparison, it can be seen that the carbon quantum dots prepared by combining anhydrous citric acid with L-lysine are more conducive to the scale inhibition performance of the scale inhibition dispersant of the present invention on calcium carbonate scale. Comparative Example 8 shows the scheme without adding polyepoxysuccinic acid, in which case, its scale inhibition rate is lower. Referring to Example 1 to Example 8, under the formulation of the present invention, the scale inhibition efficiency for calcium carbonate scale is relatively high, and the scale inhibition rate at 100°C is even higher than that at 80°C. This may be because, with the increase in temperature, the chitosan-polyethylene glycol graft copolymer on the surface of the mesoporous silica composite material expands or undergoes conformational changes, which helps to release the carbon quantum dots from the mesoporous silica composite material. In this process, sodium tannate can promote this release and maintain the effective dispersibility of the carbon quantum dots after the release, thereby ensuring that it has a sufficient scale inhibition rate. It can be seen that the scale inhibition dispersant of the present invention achieves its efficient calcium carbonate scale inhibition effect at least through the synergistic effect of the mesoporous silica composite material, sodium tannate and polyepoxysuccinic acid. In addition, it should be noted that the citric acid added to the components of the scale inhibitor and dispersant of the present invention can, on the one hand, adjust the pH value of the formula, thereby ensuring the stability and activity of each component. On the other hand, in an aqueous solution, citric acid can undergo a chelating reaction with metal ions such as calcium and magnesium in water, so that the calcium and magnesium ions exist in the solution in a complex state, rather than being free and combining with each other to form scale, thereby effectively preventing the formation of scale. In addition, citric acid can dissolve scale adsorbed on the surface of the mesoporous silica composite material, so that the adsorption sites of the composite material can be continuously utilized, thereby improving the removal efficiency of metal ions. After citric acid chelates the metal ions, sodium tannate can further prevent the aggregation and precipitation of the chelated products, thereby maintaining the dispersion stability of the system. In addition, it should be noted that the chitosan-polyethylene glycol grafted copolymer obtained by grafting polyethylene glycol onto chitosan has improved hydrophilicity and enhanced biocompatibility, biodegradability and stability. When it is coated on the surface of mesoporous silica, it helps the mesoporous silica composite material to be well dispersed in the aqueous phase system, thereby providing sufficient scale inhibition effect at high temperature.In addition, referring to Example 9 and Example 10, the amount of the mesoporous silica composite material used for coating is also very important. The amount in Example 9 is less than that in Example 2, and only part or a small part of the surface of the mesoporous silica is coated, which may result in a large amount of carbon quantum dots being released from the mesoporous silica composite material at 80°C, thereby making the scale inhibition rate at this temperature significantly higher than that of Examples 1 to 8, and at higher temperatures, the carbon quantum dots are released in large quantities and quickly, and agglomeration may occur, which leads to a significant decrease in the scale inhibition rate, but its scale inhibition rate is still higher than that of the comparative example; the amount of chitosan-polyethylene glycol graft copolymer used for coating in Example 10 is more than that in Example 2, which reduces the release rate of carbon quantum dots from the mesoporous silica. Therefore, its scale inhibition rate is lower than that of other examples, but the overall scale inhibition effect is still higher than that of the comparative example. It should also be noted that at 120°C, the scale inhibition rate of each embodiment is lower than that at 100°C, indicating that the influence of temperature is already very significant at this time. Although the release of carbon quantum dots may further increase, it can no longer offset the influence of temperature.

[0080] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A scale inhibitor dispersant, characterized in that: The scale inhibitor and dispersant comprises the following raw material components by weight: 15 to 20 parts of a mesoporous silica composite material, 5 to 8 parts of citric acid, 0.2 to 0.5 parts of sodium tannate, 8 to 12 parts of polyepoxysuccinic acid and 70 to 80 parts of deionized water; wherein the mesoporous silica composite material comprises mesoporous silica and a chitosan-polyethylene glycol graft copolymer at least partially coated on the surface of the mesoporous silica, and carbon quantum dots are embedded in the mesopores of the mesoporous silica.

2. A scale inhibitor and dispersant according to claim 1, characterized in that: The chitosan-polyethylene glycol graft copolymer accounts for 5% to 10% of the total weight of the mesoporous silica composite material.

3. A scale inhibitor and dispersant according to claim 1 or 2, characterized in that: In parts by weight, the raw material components of the scale inhibitor and dispersant contain 0.3 parts of sodium tannate.

4. A method for preparing a scale inhibitor and dispersant, which is used to prepare a scale inhibitor and dispersant according to any one of claims 1 to 3, characterized in that: The method comprises the following steps: S1. preparing a mesoporous silica composite material; S2. Evenly mix the prepared mesoporous silica composite material with citric acid, sodium tannate, polyepoxysuccinic acid and deionized water in a predetermined ratio to obtain the product.

5. The method for preparing a scale inhibitor and dispersant according to claim 4, characterized in that: The steps of preparing the mesoporous silica composite material include: The first step is to prepare mesoporous silica with a mesoporous structure; The second step is to obtain a pure carbon quantum dot solution; The third step is to embed carbon quantum dots into the pores of the mesoporous silica; The fourth step is to prepare chitosan-polyethylene glycol graft copolymer and coat it on the surface of mesoporous silica embedded with carbon quantum dots, thereby obtaining the mesoporous silica composite material.

6. The method for preparing a scale inhibitor and dispersant according to claim 5, characterized in that: In the second step, carbon quantum dots were prepared using anhydrous citric acid and L-lysine at a molar ratio of 10~15:

1.

7. Use of the scale inhibitor and dispersant according to any one of claims 1 to 3 in industrial circulating water.

Citation Information

Patent Citations

  • Amphipathy polyethylene glycol stem grafting chitosan copolymer and preparation method and application thereof

    CN102504046A

  • Mesoporous silica / carbon dot nanometer composite and preparation method thereof

    CN104877677A